Anderson-Hynes Pyeloplasty in Children: Nonintubated Versus Intubated (Bangladesh Journal of Child Health, 2012)
Objective: To compare between nonintubated versus intubated Anderson-Hynes (AH) pyeloplasty in children.Study Design: Prospective studyStudy place: Department of Paediatric Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh and some private clinics of Dhaka city. Study period: March 2001 to December 2008.Subjects: A total of 75 patients were included in this study. They were divided in two groups. Nonintubated Anderson-Hynes pyeloplasty was done in 45 patients and intubated Anderson-Hynes pyeloplasty was done in 30 patients.Results: The anastomotic leakage of urine, urinary tract infection, hospital stay and improvement of differential renal function were assessed post operatively in both nonintubated and intubated groups. This study showed that there was no anastomotic failure and no post operative urinary tract infection in either group. The percentage of improvement of differential renal function is almost same in both the groups. The post operative hospital stay was markedly reduced in nonintubated Anderson-Hynes pyeloplasty. In this study the post operative hospital stay in nonintubated group was average 6 days and it was average 16.5 days in intubated group.Conclusion: From this study it may be concluded that the effects of nonintubated AH pyeloplasty is as good as intubated one but an additional advantage of significantly less post operative hospital stay was observed in nonintubated group.DOI: http://dx.doi.org/10.3329/bjch.v35i2.10378  Bangladesh J Child Health 2011; Vol 35 (2): 59-61